1987
DOI: 10.1136/oem.44.4.228
|View full text |Cite
|
Sign up to set email alerts
|

Some peculiarities of the pulmonary phagocytotic response: dust retention kinetics and silicosis development during long term exposure of rats to high quartz dust levels.

Abstract: Rats were exposed to quartz dust (about 90 mg/m3) for five hours a day, five times a week either throughout the 48 weeks of the experiment or for a total of 40 weeks plus eight weeks of "rest."Cytological study of bronchoalveolar lavage showed that at a certain level of silicotic changes in the lungs, a pronounced breakdown in pulmonary dust clearance by macrophages could be observed. There was, however, a concomitant compensatory increase in the contribution to pulmonary phagocytosis by the neutrophil leukocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 11 publications
1
23
0
Order By: Relevance
“…They are hardly always living with chronic inflammation of the respiratory system. Meantime, it is long ago that we [96][97][98][99][100] found fairly strong reasons for considering the NL recruitment response to be an important mechanism of partial compensation for the damage caused by cytotoxic micrometric particles to AMs, the main effector of the pulmonary clearance. A mathematical multi-compartmental model of pulmonary region clearance which comprised just this compensatory mechanism simulated very well the pulmonary retention of dusts of varying degrees of cytotoxicity (quartzite rock, titanium dioxide, standard quartz DQ12) under long-term inhalation exposure as well as a decrease in this retention under the effect of such potent protectors of the macrophage against particle cytotoxicity as glutamate.…”
Section: Some Inferences From In Vivo Experiments With Metallic Nanopmentioning
confidence: 99%
See 1 more Smart Citation
“…They are hardly always living with chronic inflammation of the respiratory system. Meantime, it is long ago that we [96][97][98][99][100] found fairly strong reasons for considering the NL recruitment response to be an important mechanism of partial compensation for the damage caused by cytotoxic micrometric particles to AMs, the main effector of the pulmonary clearance. A mathematical multi-compartmental model of pulmonary region clearance which comprised just this compensatory mechanism simulated very well the pulmonary retention of dusts of varying degrees of cytotoxicity (quartzite rock, titanium dioxide, standard quartz DQ12) under long-term inhalation exposure as well as a decrease in this retention under the effect of such potent protectors of the macrophage against particle cytotoxicity as glutamate.…”
Section: Some Inferences From In Vivo Experiments With Metallic Nanopmentioning
confidence: 99%
“…It was found that this recruitment is controlled by the mass of macrophage breakdown products (MBP) and especially by their lipid fraction. [96][97][98][99][100] Therefore, the more cytotoxic for AMs are particles deposited in the lungs (or the higher the dose of MBPs obtained by aseptic freezingthawing or ultrasonic destruction of non-activated peritoneal macrophages and then instilled intratracheally), the higher is a count ratio of NLs to AMs in the BALF. Therefore this ratio (NL/AM) can be used as an indirect but highly informative comparative in vivo index for the cytotoxic action of any low-soluble particle, and it was demonstrated that ranking of dusts by this index was well correlated with the ranking of their cytotoxicity based on the Trypan blue exclusion test for cell viability in vitro.…”
mentioning
confidence: 99%
“…A special mathematical analysis (55) and a long-term inhalation experiment corroborating its conclusions (25,56) demonstrated that such a dependece really exists. As concerns prophylactic efficiency of the defense with time factor against silicosis, those conclusion are briefly as follows.…”
Section: Nutritional Factors and Food Additivesmentioning
confidence: 54%
“…Experimental data that demonstrate that this damage is partly compensated by enhanced contribution of neutrophil leukocytes to phagocytosis of cytotoxic particles and, thus, to their clearance from lungs, have been summarized previously (24). Later it was shown that the role of this compensatory mechanism became still more important under long-term quartz dust inhalation exposure (25). When the development of silicosis in lungs of exposed rats reached a certain level, the macrophage mechanism of phagocytosis became so grossly damaged that the dif-ference between bronchoalveolar lavage (BAL) macrophage counts of exposed and control rats, quite considerable at early stages of the experiment, completely disappeared.…”
Section: Autonomic Nervous System and Selection Of Silica-resistant Imentioning
confidence: 89%
See 1 more Smart Citation